2009
DOI: 10.1111/j.1463-1326.2009.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of n‐3 PUFA reduces weight gain and improves postprandial lipaemia and the associated inflammatory response in the obese JCR:LA‐cp rat

Abstract: Acute dietary n-3 PUFA dietary supplementation can improve fasting as well as postprandial lipid metabolism and components of the associated inflammatory response in the JCR:LA-cp rat. Further, moderate dose n-3 PUFA supplementation may reduce corresponding body weight during conditions of hypercholesterolaemia and/or modulate inflammation associated with obesity and the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 60 publications
10
45
1
2
Order By: Relevance
“…This was in contrast, again, with Simão et al [30]. Our results are in line with what reported by Hassanali et al [47] in rats: acute dietary n-3 PUFA dietary supplementation can improve fasting as well as post-prandial lipid metabolism and components of the associated inflammatory response in the JCR/LA-cp rat.…”
Section: Discussioncontrasting
confidence: 54%
“…This was in contrast, again, with Simão et al [30]. Our results are in line with what reported by Hassanali et al [47] in rats: acute dietary n-3 PUFA dietary supplementation can improve fasting as well as post-prandial lipid metabolism and components of the associated inflammatory response in the JCR/LA-cp rat.…”
Section: Discussioncontrasting
confidence: 54%
“…Our laboratory has previously reported that dietary fatty acid composition alters haptoglobin levels of the cp/cp male rat following an oral fat challenge (16). The reduction of postprandial plasma haptoglobin levels observed in rimonabant-treated rats (Fig.…”
Section: Rimonabant and Proinflammationmentioning
confidence: 88%
“…We conclude that rimonabant improves renal disease and intestinal lipid oversecretion associated with an animal model of the metabolic syndrome that appears to be independent of hyperinsulinemia or macrovascular dysfunction. metabolic syndrome; chylomicron overproduction; inflammation; microalbuminuria; glomerular sclerosis; plasminogen activator inhibitor-1; apolipoprotein B48 EXCESSIVE WEIGHT GAIN, PARTICULARLY in the form of abdominal (visceral) adipose tissue, is a major public health problem in prosperous societies worldwide (16,65). The resultant abdominal obesity has driven a developing epidemic of prediabetic insulin resistance and cluster of associated metabolic abnormalities that are termed the metabolic syndrome (9, 35).…”
mentioning
confidence: 99%
“…Simopoulos (2016) menyatakan bahwa omega 3 mampu menghalangi terbentuknya enzim lipogen yang berperan dalam pembentukan lemak yang akan terakumulasi pada sel adiposa. Penelitian yang dilakukan oleh Hassanali et al (2010) menjelaskan bahwa pemberian suplemen omega 3 mampu menurunkan berat badan pada kondisi hiperkolesterolemia, sejalan dengan penelitian yang dilakukan oleh Ruzickova et al (2004) dan Mendez-Sanchez et al (2001). Hasil analisis ANOVA menunjukkan bahwa tidak terdapat perbedaan yang signifikan antar perlakuan.…”
Section: Perubahan Bobot Tikusunclassified